Effect of curing: conditions on strength and durability of high-performance concrete - Canpolat, F.; Naik, T. R. (ELSEVIER SCIENCE BV, 2017)
This paper describes the effects of variable curing temperatures on compressive strength and sulfate resistance of high-strength, high-performance concrete. Two different concrete mixtures were proportioned to attain the 56-day compressive strength of about 70 MPa upon moist-curing. One mixture contained more quantity of ASTM Class C fly ash than the other one. For each mixture, one set of specimens was cured in a standard moist-curing room at 23 degrees C and 100% relative humidity; another set of specimens was sealed in plastic bags and cured in an elevated, Variable-Temperature Curing Environment (VTCE). The average temperature of the VTCE oscillated between about 30 C and 41 C once per day. This study revealed that the VTCE-cured concrete did not significantly exhibit different compressive strength or ability to resist sulfates attack compared to the standard moist-cured specimens. Thus, it was concluded, based on the results of this research, that additional effort to stabilize higher curing-temperatures would be necessary for field-cured concrete. (C) 2017 Sharif University of Technology. All rights reserved.
Keywords: Compressive strength; Curing; Fly ash; High-performance concrete; Sulfate resistance; Temperature; FLY-ASH; Engineering